2022
DOI: 10.3390/genes13112133
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Protects against Myocardial Ischemia–Reperfusion Injury by Inhibiting GSDMD-Mediated Pyroptosis

Abstract: Pyroptosis serves a crucial function in various types of ischemia and reperfusion injuries. Oridonin, a tetracycline diterpene derived from Rabdosia rubescens, can significantly inhibit the aggregation of NLRP3-mediated inflammasome. This experiment is aimed at investigating the effect of oridonin on pyroptosis in mice cardiomyocytes. Based on the models of myocardial ischemia/reperfusion (I/R) and hypoxia/reoxygenation (H/R), Evans Blue/TTC double staining, TUNEL staining, and Western blotting were applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The musculoskeletal benefits of exercise are clearly beneficial for middleaged and older adults (Lim and Goh, 2022;Schaun et al, 2022), and studies have concluded that comprehensive content exercise helps by improving muscle size, muscle strength, balance and physical function in older adults that have decreased because of age (Shahtahmassebi et al, 2022). Due to changing lifestyles and increased academic stress, physical and mental health problems among college students have become increasingly serious, and there are systematic evaluations of qigong exercises considered to improve physical and mental health of college students, with no significant effects on muscle strength found (Lin et al, 2022b). There is also a study of the effects of 8 weeks of resistance training on physical performance and body composition in adolescent athletes, with significant benefits in muscular endurance, strength and static balance (Fayazmilani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The musculoskeletal benefits of exercise are clearly beneficial for middleaged and older adults (Lim and Goh, 2022;Schaun et al, 2022), and studies have concluded that comprehensive content exercise helps by improving muscle size, muscle strength, balance and physical function in older adults that have decreased because of age (Shahtahmassebi et al, 2022). Due to changing lifestyles and increased academic stress, physical and mental health problems among college students have become increasingly serious, and there are systematic evaluations of qigong exercises considered to improve physical and mental health of college students, with no significant effects on muscle strength found (Lin et al, 2022b). There is also a study of the effects of 8 weeks of resistance training on physical performance and body composition in adolescent athletes, with significant benefits in muscular endurance, strength and static balance (Fayazmilani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…But inflammasomes are also found in cardiomyocytes themselves [117][118][119][120][121]. Indeed, the hypoxia/reoxygenation of rat cardiomyocytes leads to the release of the N-terminal fragment of GSDMD and cas-1, while their release is significantly curtailed when NLRP3 is inhibited [122]. Furthermore, after NLRP3 inhibition, the expected loss of membrane integrity and the release of LDH as a marker of membrane failure are no longer apparent.…”
Section: Gasdermin D and Caspase-1 Play Pivotal Roles In The Pyroptos...mentioning
confidence: 99%
“…Oridonin (Ori) is a natural organic compound of kaurene diterpenoids extracted from Isodon rubescens. 1,2 Ori has antitumor, [3][4][5] antibacterial, [6][7][8] antiangiogenesis, 9 delayed aging, 10 and many other biological activities. 11 It can induce apoptosis, 12,13 autophagy, and cell cycle arrest of tumor cells by regulating multiple molecular signal pathways, 14,15 inhibiting the proliferation and metastasis of many cancer cells.…”
Section: Introductionmentioning
confidence: 99%